The improved rice management package '1 Must Do-5 Reductions' (1M5R) reached 104,448 smallholder rice farmers and was adopted on 114,870 ha in the Mekong River Delta of Vietnam - CGIAR Research Program on Rice (2021)
After five years of the promotion of the improved rice management package '1 Must Do-5 Reductions' (1M5R), the package was reached by 104,448 smallholder rice farmers and adopted on 114,870 ha in the Mekong River Delta of Vietnam. More importantly, of the farmers who used either 3R3G (the precursor technology) or 1M5R, there is evidence of higher incomes, of between 19% to 36%, across different provinces.